Transformation of smallholder beef cattle production in Vietnam - Stür, Werner W.; Khanh, T.T.; Duncan, Alan J. (Informa UK Limited, 2013)
This research describes and analyses how smallholder crop livestock farmers in rural Ea Kar, Vietnam, were able to take advantage of the rising demand for meat in urban centres and transform cattle production from a traditional, extensive grazing system to a more intensive, stall-fed system that supplied quality meat to urban markets. The traditional grazing system produced low-quality animals that could only be sold for local consumption. Introduction of the concept of farm-grown fodder production enabled farmers to produce fatter animals, achieving higher sale prices, and reduce labour inputs by moving from grazing to stall-feeding. These benefits convinced farmers, traders and local government that smallholder cattle production could be a viable enterprise and so stimulated stakeholder interest. Within 10 years, the way that cattle were produced and marketed changed considerably. By 2010, more than 3,000 smallholders had adopted farm-grown forages and stall-feeding, and many produced high-quality beef cattle. Traders had been able to develop access to urban markets as farmers were able to produce animals that satisfied the stringent quality requirements of urban markets. In addition to the underlying driver of strong market demand for quality meat, several factors contributed to this transition: (i) a convincing innovation – the use of farm-grown fodder – that provided immediate benefits to farmers and provided a vision for local stakeholders; (ii) a participatory, systems-oriented innovation process that emphasised capacity strengthening; (iii) a value chain approach that linked farmers and local traders to markets; (iv) the formation of a loosely structured coalition of local stakeholders that facilitated and managed the innovation process; and (v) technical support over a sufficiently long time period to allow innovation processes to become sustainable.